2006
DOI: 10.2466/pms.102.3.788-790
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Comparison of Anxiety Direction and Burnout over Time

Abstract: The purpose of this study was to assess if athletes who perceived their trait anxiety to be debilitative to performance also experienced higher burnout over a competitive season. Volunteers were 53 NCAA Division I and II male (n = 14) and female (n = 39) athletes, ages 18 to 23 years. Participants completed a trait version of the Competitive State Anxiety Inventory-2D once and the Athlete Burnout Questionnaire three times during the season. A 2 (anxiety direction group) x 3 (time of season) multivariate analys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
7
0
3

Year Published

2010
2010
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 6 publications
5
7
0
3
Order By: Relevance
“…This is not a surprising result, and similar findings have been reported in a number of research studies [19, 38]. Wiggins et al [38] reported that basketball players who experienced lower anxiety were less discouraged and less stressed during competition, compared to basketball players who reported higher anxiety. Our previous research noted that elite baseball and soccer player groups showed less state anxiety, compared to general player groups [19].…”
Section: Discussionsupporting
confidence: 83%
“…This is not a surprising result, and similar findings have been reported in a number of research studies [19, 38]. Wiggins et al [38] reported that basketball players who experienced lower anxiety were less discouraged and less stressed during competition, compared to basketball players who reported higher anxiety. Our previous research noted that elite baseball and soccer player groups showed less state anxiety, compared to general player groups [19].…”
Section: Discussionsupporting
confidence: 83%
“…These are not surprising results and have been reported in many studies 30,31. Hardy30 reported that stress would debilitate the function of psychological skills (goal-setting, imagery, self-talk, and relaxation skills) which were thought to enhance the performance of athletes.…”
Section: Discussionsupporting
confidence: 63%
“…5,6,[29][30][31] Conversely, some negative psychology constructs, such as anxiety and chronic stress, are related to an increase in the tendency of athlete burnout. 25,32,33 Taking into consideration this intensification of interest in burnout in sports, it becomes important to determine whether this negative experience is also related to the way athletes evaluate their activity. In our study, we highlight the construct of cognitive appraisal as a possible mediator between trait anxiety and burnout.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, Hypothesis 1 stated that trait anxiety is positively related to burnout, threat perception is positively related to burnout, and challenge perception is negatively related to burnout. There is some empirical evidence that sustains this hypothesis, suggesting that higher levels of anxiety are related to psychological problems in athletes, 27,[32][33][34] and that higher levels of trait anxiety predispose athletes to the risk of burnout. 25,35,36 This hypothesis is also supported by the conceptual models presented before, which suggested the central role of cognitive appraisal in the athletes' feelings of burnout, 4 and the differential effects of challenge and threat states in performance and adaptation to stress in sports.…”
Section: Introductionmentioning
confidence: 99%